THE VOUCHER PROGRAMME AS A CHALLENGE FOR SOCIAL WORK TEACHING - Tetyana Semigina; Oksana Pozhidayeva (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The study presents the experiences of introducing the so-called educational voucher system for adults over 45 years old in Ukraine. Based on the content analysis of academic documents, the survey of adult students and interviews with educators, the study examines motivation, learning process and self-evaluation of the social work training among students who already have a higher education. The research findings demonstrate that the students over 45 years old were motivated to get an additional university degree in social work mainly because of a need for self-realisation, and not because of market demands. In the survey, 20 out of 25 respondents claimed that they had an idea of what social work was as a profession prior to beginning their studies and hardly are going to work within the new profession. Adult students highly prize positive in-class atmosphere and prefer to study in a group of peers; they more or less easily adjust to the new learning environment. At the same time, teaching had to challenge the expectations of adult learners with learning arrangements that are non-traditional for them. The research adds another layer to the professional debate on the social work education model by focusing on 45+ students, competences and ethical behaviour mastering.